Digitized droop control of a high gain primitive converter—General performance analysis for smart city lighting application. (3rd September 2020) - Kannan, Subha Sharmini; Krishnasamy, Vijayakumar
Abstract: This article presents the detailed behavioral analysis of the reduced equation DC droop controller being adapted to the primitive high gain converter designed for DC loads. The article discusses the operation in its open and closed loop modes, voltage, and current control modes as part of the simulation study. The converter mode of operation is continuous in all. Graphical portrayals of statistical results describe the effectiveness of the controller against a standard proportional integral (PI) controller in time and frequency domain. The results substantiate that the DC droop control is superior in terms of efficiency, line regulation, dynamism, and current sharing and stability.